Mapping Vertical Land Motion in Challenging Terrain: Six‐Year Trends on Tutuila Island, American Samoa, With PS‐InSAR, GPS, Tide Gauge, and Satellite Altimetry Data. Issue 23 (5th December 2022) - Huang, Stacey A.; Sauber, Jeanne M.; Ray, Richard
Abstract: Sea level rise is a major challenge facing coastlines worldwide and can be strongly exacerbated by land subsidence. However, detailed characterization of vertical land motion (VLM) is limited for many tectonically active islands, as many remote sensing methods are hindered by dense vegetation and thick cloud cover. In American Samoa, strong post‐seismic deformation from the 2009 Samoa‐Tonga earthquake has increased flooding, but large uncertainties remain in hazard forecasting as only point measurements of VLM have been available. Here, we present novel VLM results over Tutuila, the largest and most populated island in American Samoa, using interferometric synthetic aperture radar, GPS, tide gauge, and satellite altimetry data. Measurements cover populated areas, with subsidence rates of 6–9 mm/yr and uncertainties of <1 mm/yr; the highest rates lie along the coastlines. We find differences in rate changes across the island, suggesting that local processes need to be well‐constrained for effective flood forecasting efforts. Plain Language Summary: Small islands in earthquake‐prone regions are particularly affected by rising sea levels. Events before, during, and after an earthquake can drastically increase how quickly the ground surface changes, potentially multiplying the severity and extent of rising waters. Designing solutions to combat these effects therefore requires knowing how much the ground is sinking and where. However, broad and accurate measurements of deformation can be difficult, especially on small islands that are densely covered with vegetation and clouds. American Samoa is a one such community that still lacks comprehensive data of how much and where the ground is sinking. In this paper, we present novel results of 6‐year trends of vertical land motion over the largest and most populated island in American Samoa, Tutuila, using a multi‐sensor approach leveraging interferometric synthetic aperture radar, GPS, tide gauge, and satellite altimetry data. Our results cover most of the populated areas, which we find are subsiding at rates of 6–9 mm/yr with uncertainties of <1 mm/yr. The highest rates of deformation lie along the coastlines. We find differences in rate changes across the island, suggesting that effective flood forecasting requires a comprehensive understanding of diverse contributions to local subsidence. Key Points: Redundant persistent scatterer‐interferometric synthetic aperture radar analysis, with GPS and joint tide gauge/satellite altimetry data, reveals coastal vertical land motion trends despite challenging terrain Subsidence rates of 6–9 mm/yr are observed on Tutuila Island from late‐2015 to mid‐2022 Locations of stronger subsidence are identified at Pago Pago International Airport and Pago Pago Harbor